PENINGKATAN KOMPETENSI PROFESIONAL GURU MELALUI PELATIHAN MODEL-MODEL PEMBELAJARAN INOVATIF - Sri Sumaryati, - (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2013)
The purposes of this activity are: (1) Enhance the ability of teachersto create a fun learning atmosphere for students. (2) Cultivating teachers toimplement innovative learning, creative, effective and fun in every activitypembelajaran. (3) Enhancing professional competence and pedagogy ofteachers, especially in implementing innovative learning models.The method used consists of (a) Extension is intended to increaseknowledge and understanding of the innovative learning models, (b)training, which is done by giving a chance to practice learning models thathave been received. (c) Assistance, intended as a follow-up of this serviceactivities. Assistance to teachers can be advisory to the problems faced inschools.The results of this activity are: (1) 90% of participants attending thetraining and mentoring diligently performed 4 times. (2) 75% are able todraw up lesson plans on the subject matter by using a model of innovativelearning.